Do More Strikes Mean a Stronger Working Class's Agency: A Comparative Study in Post‐Socialist China. (March 2017) - Lin, Jake
Abstract : Workers' agency is important to understand the Chinese working class's formation and gauge its capacity to forge transformative social and political movements. Recent labor study literature posits that class inequality and volatile capital movement leads to stronger labor resistance in post‐socialist China. Drawing on some of the theories on class consciousness and agency, this article re‐conceptualizes workers' agency, which is broken down into behavioral and cognitive agencies. It examines Chinese workers' cognitive agency in the megacities and lower‐tier cities via statistical survey data. This analysis of cognitive agency is new to the Chinese labor study. I argue that a relatively low class identification, poor understanding of democracy and politics, and weak sense of solidarity combine to reveal a new working class in post‐socialist China that, in general, shows both weak cognitive agency and growing conservativism. This distinction of workers' behavioral and cognitive agency is vital as it may eventually challenge all labor interest parties to re‐think their current strategies of labor engagement and organization.